Standard specification for Steel, Strip, Carbon (0.25 Maximum Percent), Cold-Rolled (American Society for Testing and Materials, 2008)
This specification covers cold-rolled carbon steel strip in cut lengths or coils, furnished to closer tolerances than cold rolled carbon steel sheet, with specific temper, with specifific edge or specific finish, and in sizes